Sleep Spindle Characteristics in Obstructive Sleep Apnea Syndrome (OSAS) - Mohammadi, Hiwa; Aarabi, Ardalan; Rezaei, Mohammad; Khazaie, Habibolah; Brand, Serge (Frontiers in Neurology, 2021)
Background: We compared the density and duration of sleep spindles topographically in stage 2 and 3 of non-rapid eye movement sleep (N2 and N3) among adults diagnosed with Obstructive Sleep Apnea Syndrome (OSAS) and healthy controls. Materials and methods: Thirty-one individuals with OSAS (mean age: 48.50 years) and 23 healthy controls took part in the study. All participants underwent a whole night polysomnography. Additionally, those with OSAS were divided into mild, moderate and severe cases of OSAS. Results: For N2, sleep spindle density did not significantly differ between participants with and without OSAS, or among those with mild, moderate and severe OSAS. For N3, post-hoc analyses revealed significantly higher spindle densities in healthy controls and individuals with mild OSA than in those with moderate or severe OSAS. Last, in N2 a higher AHI was associated with a shorter sleep spindle duration. Conclusion: OSAS is associated with a significantly lower spindle density in N3 and a shorter spindle duration in N2. Our results also revealed that, in contrast to moderate and severe OSAS, the sleep spindle characteristics of individuals with mild OSAS were very similar to those of healthy controls.